The two-way of imagination and empathy on the path to creativity - Sobrinho, Asdrúbal Borges Formiga; Sanmartin, Stela Maris (Farol, 2023)
To discuss creativity in the domain of expression of the Arts, we deal with the creation process based on interactions between: author and work, mediated by the materiality of the creative action; author and audience, mediated by the materiality of the work; audience and work, mediated by the physical or imaginary body movement expected of the spectator. We take as an example the journey of creating an artist's work, when conceiving an installation already considering possible impacts on the audience. The journey involves bodily, affective and mental movements that are part of the exercise of empathy. Its result can transform materials, techniques, meanings and lives. Depending on the values present in the message and the values attributed to the work, it can impact the artist himself, his audience, the domain of the Arts, a society and a culture. We conclude the reflection by crediting the continuum of creativity to the poetics constructed and reconstructed, imagined and materialized, created and recreated by the artist.